Literature Review on the Use of Electronic Modules in Independent Learning in Higher Education - Ade Holisoh; John Pahamzah; Sholeh Hidayat (Journal of General Education and Humanities, 2025)
The use of electronic modules in the implementation of Independent Learning Independent Campus (MBKM) in higher education has proven to be effective in improving the quality of learning and student learning outcomes. Research shows that electronic modules, such as those based on Project Based Learning (PjBL), hypercontent, and e-pub, provide flexible interactivity and support independent and collaborative learning. The study reveals the development of entrepreneurship modules in the ISI Yogyakarta Music Education Study Program, which has been highly successful. The module has been validated with a high score of 93, meeting the standards of practitioners, academics, and communication experts. It has also improved students' knowledge and motivation in the creative industry. The module's structure and content make learning more straightforward, and students have provided positive feedback. It is also relevant to the graduate profiles of the program, including art managers, consultants, and music educators. This study highlights the importance of entrepreneurship modules in meeting students' academic needs and empowering them in the business world. This module also helps students master difficult concepts, increase their interest and practical skills, and motivate them to face work challenges. In response to MBKM, the electronic module allows students to learn flexibly, be relevant to the real world, and develop 21st-century skills. Therefore, the development more interactive modules and technology-based applications needs to be improved, and lecturers and students must be trained to utilize this technology. Collaboration with industry and educational technology developers is also important to create modules that suit the needs of the world of work. Continuous evaluation and innovation are needed so that the module remains relevant to technological developments and future educational demands.